Plasmodium falciparum Merozoite Surface Protein 6 Is a Dimorphic Antigen - Pearce, J. Andrew (American Society for Microbiology, 2004)
Merozoite surface protein 1 (MSP1) is a highly polymorphic Plasmodium falciparum merozoite surface protein implicated in the invasion of human erythrocytes during the asexual cycle. It forms a complex with MSP6 and MSP7 on the merozoite surface, and this complex is released from the parasite around the time of erythrocyte invasion. MSP1 and many other merozoite surface proteins contain dimorphic elements in their protein structures, and here we show that MSP6 is also dimorphic. The sequences of eight MSP6 genes indicate that the alleles of each dimorphic form of MSP6 are highly conserved. The smaller 3D7-type MSP6 alleles are detected in parasites from all malarious regions of the world, whereas K1-type MSP6 alleles have only been detected in parasites from mainland Southeast Asia. Cleavage of MSP6, which produces the p36 fragment in 3D7-type MSP6 and associates with MSP1, also occurs in K1-type MSP6 but at a different site in the protein. Anti-3D7 MSP6 antibodies weakly inhibited erythrocyte invasion by homologous 3D7 merozoites but did not inhibit a parasite line expressing the K1-type MSP6 allele. Antibodies from hyperimmune individuals affinity purified on an MSP3 peptide cross-reacted with MSP6; therefore, MSP6 may also be a target of antibody-dependent cellular inhibition.